2014
DOI: 10.1371/journal.pone.0092457
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of HuR in the Post-Transcriptional Regulation of Interleukin-3 in T Cells

Abstract: Human Interleukin-3 (IL-3) is a lymphokine member of a class of transiently expressed mRNAs harboring Adenosine/Uridine-Rich Elements (ARE) in their 3' untranslated regions (3'-UTRs). The regulatory effects of AREs are often mediated by specific ARE-binding proteins (ARE-BPs). In this report, we show that the human IL-3 3'-UTR plays a post-transcriptional regulation role in two human transformed cell lines. More specifically, we demonstrate that the hIL-3 3'-UTR represses the translation of a luciferase report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…HuR regulates cellular responses to differentiation, senescence, inflammatory factors, and immune stimuli by tightly controlling the post-transcriptional fate of specific mRNAs ( 9 12 ). Notably, HuR binds to and regulates the half-life of mRNAs and/or the translation of mRNAs encoding key inflammatory cytokines and interleukins, such as tumor necrosis factor-α (TNFα) ( 13 ) and interleukin IL-1β, IL-3 ( 14 ), IL-6 ( 15 ), IL-8, IL-10, IL-4, CXCL1 ( 16 18 ), in turn governing the development and maturation of B and T lymphocytes ( 19 , 20 ). HuR is highly expressed in many cancer types, and is believed to promote tumorigenesis by interacting with mRNAs encoding proteins implicated in cell proliferation and survival, angiogenesis, invasion, pharmacoresistance and metastasis ( 21 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…HuR regulates cellular responses to differentiation, senescence, inflammatory factors, and immune stimuli by tightly controlling the post-transcriptional fate of specific mRNAs ( 9 12 ). Notably, HuR binds to and regulates the half-life of mRNAs and/or the translation of mRNAs encoding key inflammatory cytokines and interleukins, such as tumor necrosis factor-α (TNFα) ( 13 ) and interleukin IL-1β, IL-3 ( 14 ), IL-6 ( 15 ), IL-8, IL-10, IL-4, CXCL1 ( 16 18 ), in turn governing the development and maturation of B and T lymphocytes ( 19 , 20 ). HuR is highly expressed in many cancer types, and is believed to promote tumorigenesis by interacting with mRNAs encoding proteins implicated in cell proliferation and survival, angiogenesis, invasion, pharmacoresistance and metastasis ( 21 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is another RNA binding protein that recognizes AU-rich sequences located in the 3ʹ-UTRs of target genes and protects the respective mRNAs from degradation [28][29][30]. ELAVL1 also plays role in regulation of IL-3 expression [31]. Abundance of ELAVL1 decreased in both cytoplasm and nucleus after the combined treatment (Figure 4, column 3).…”
Section: Resultsmentioning
confidence: 99%
“…For example, overexpression of HuR did not stabilize CSF2 and IL-3 ARE reporters, while a fos ARE reporter was stabilized [67]. Knockdown of HuR in Jurkat cells produced a very mild (1.2 fold) destabilizing effect on a IL-3 UTR reporter [58], likely insufficient to explain the drastic decrease in its mRNA levels seen in the HuR KO. Studies with IL-2 showed that HuR overexpression failed to stabilize GFP-IL-2 reporter halflife, and HuR did not bind to IL-2 mRNA affinity resin [68].…”
Section: Discussionmentioning
confidence: 97%
“…However, the regulatory mechanism in Jurkat and 293 cells is a surprise that is inconsistent with some of the previous data: HuR does not appreciably regulate the 3′ UTRs of CSF2, IFNG, IL-2, IL-3, IL-13, and TNF mRNAs in 293 cells, and the major IL-2 and TNF cytokine mRNAs in Jurkats. Previously, HuR was shown to bind AU-rich sequences in TNF, CSF2 and IL-3 UTRs [38][39][40][41][42][43]45,58] and HuR immunoprecipitation was shown to enrich IL-2, IL-13, INFg, and TNF mRNA from lysates relative to IgG controls [8,35,44,59,60]. Together with reporter data demonstrating that overexpression of HuR causes stabilization of TNF, IL-13, and CSF2 UTR fragment or IL-3 whole mRNA reporters [43,44,46,47], these observations generated a prevailing model that HuR regulates mRNA stability through the 3′ UTR.…”
Section: Discussionmentioning
confidence: 99%